2020
DOI: 10.1021/acsnano.9b08952
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Microspines for a High-Performance Spray Ti3C2Tx MXene-Based Piezoresistive Sensor

Abstract: Recently, wearable and flexible pressure sensors have sparked tremendous research interest, and considerable applications including human activity monitoring, biomedical research, and artificial intelligence interaction are reported. However, the large-scale preparation of low-cost, high-sensitivity piezoresistive sensors still face huge challenges. Inspired by the specific structures and excellent metal conductivity of a family of two-dimensional (2D) transition-metal carbides and nitrides (MXene) and the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
300
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 410 publications
(305 citation statements)
references
References 39 publications
3
300
0
2
Order By: Relevance
“…This sensor was ultrathin, flexible, and highly sensitive, and therefore easy to attach to the skin for detecting human activities and human-computer interaction ( Fig. 17d) [178]. MXenes films can also be utilized for detecting various gases and biologically important molecule because of the active surface functional groups and layered structures.…”
Section: Other Applicationsmentioning
confidence: 99%
“…This sensor was ultrathin, flexible, and highly sensitive, and therefore easy to attach to the skin for detecting human activities and human-computer interaction ( Fig. 17d) [178]. MXenes films can also be utilized for detecting various gases and biologically important molecule because of the active surface functional groups and layered structures.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Considering these impressive electrochemical performance together with high mechanical flexibility, we design an actual use of wearable energy‐sensor system to detect the physiological signals by making the connection of FSC, Ti 3 C 2 T x MXene mechanical sensor and Bluetooth device (Figure 5 a). In this wearable system, the FSC is utilized as a high energy supply to stably power mechanical sensor, thereby efficiently monitoring the human activities with steadily physiological signals [40] . As shown in Figure 5 b (Supporting Information, Movie S1), two pulse signals of normal and after exercise are recorded by attaching the wearable system on wrist.…”
Section: Resultsmentioning
confidence: 99%
“…In this wearable system, the FSC is utilized as ah igh energy supply to stably power mechanical sensor, thereby efficiently monitoring the human activities with steadily physiological signals. [40] As shown in Figure 5b (Supporting Information, Movie S1), two pulse signals of normal and after exercise are recorded by attaching the wearable system on wrist. It was showed that the normal pulse frequency is around 78 times per min, whereas it raises to around 120 times per min with an enhanced intensity after exercise.S pecially,t hose physical signals can be read out on mobile phone in real time,w hich exhibit two significantly distinguishable peaks (strong peak indicating the systolic process and weak peak revealing the diastolic behavior).…”
Section: Methodsmentioning
confidence: 99%
“…[ 29,30 ] For example, Cheng et al. successfully fabricated an MXene‐based pressure sensor with bioinspired microspinous microstructures through a printing process, which exhibited a high sensitivity of 151.4 kPa −1 and short response time of 130 ms. [ 31 ] In addition, a single‐layer MXene has a high specific surface area and good surface hydrophilicity, which significantly enhances the force of binding with the contact substrate for better cyclic stability. Therefore, it is a good electrode material candidate for flexible devices.…”
Section: Introductionmentioning
confidence: 99%